Princess Millie and the magical mermaid - French, Vivian (London : Orchard, 2008)
Princess Millie and her friends in Daffodil Room are painting at the beach when the twins Diamonte and Gruella get trapped by the incoming tide, and Millie must turn to a little mermaid for help.
3-6.
Keywords: Princesses -- Juvenile fiction; Tiara Club (Imaginary organization) -- Juvenile fiction; Mermaids -- Fiction; Children's stories